Safety and early return to sports for early ACL reconstruction in young athletes: a retrospective study - Yamanashi, Y.; Mutsuzaki, H.; Kawashima, T.; Ikeda, K.; Deie, M.; Kinugasa, T. (Medicina, 2024)
Background and Objectives: Although previous reports have shown that early anterior cruciate ligament (ACL) reconstruction is associated with an increased risk of stiffness, recommendations for delayed surgery are based on outdated literature. The advent of arthroscopic surgery and accelerated rehabilitation protocols warrants a reexamination of the optimal surgical timing. The purpose of this study was to investigate complications during early ACL reconstruction after injury in young athletes. Materials and Methods: A total of 87 patients (27 males and 60 females) were included in this study. Patients who underwent anatomic ACL reconstruction using hamstring autografts were evaluated. Patients under 25 years of age with a Tegner activity score greater than 6 were included and classified into three groups according to the time from injury to surgical treatment: one week from injury to surgery (early group), three to six weeks from injury to surgery (normal group), and three to six months from injury to surgery (delayed group). We evaluated the rates of various complications such as graft rupture, contralateral injury, the need for manipulation for loss of ROM, infection, and fracture around the knee up to 2 years postoperatively. In addition, we investigated postoperative muscle strength, Lysholm score, Tegner activity score, and period of the return to sport from injury. Results: Patients in the delayed group were younger than those in the other groups (p = 0.009). Patients in the early group had a lower range of motion than those in the other groups preoperationly. However, the 1-month postoperative range of motion was comparable between groups. Patients in the early group had greater postoperative Tegner activity scores than those in the other groups. The period of return to sport from injury in the delayed group was longer than in the other groups. There were no statistically significant differences in the postoperative complication rate, muscle strength, or Lysholm score. Conclusions: ACL reconstruction performed 1 week from injury to surgery in young athletic patients indicated the rate of complications were not significantly different among the groups. Early ACL reconstruction with no postoperative complications may be related to early return to sports and a high level of sports.